Geostatistical assessment of heavy metals and nutrients availability in soil of oil palm plantation affected by bauxite mining - Zulkifli, Mazidah; Muhamad Tajudin, Nur Shuhada; Miskon, Mohd Fuad; Faudzi, Fikriah; Jamaludin, Nurul Mayzaitul Azwa (Malaysian Palm Oil Board, 2022)
This study describes the contamination of heavy metals (Cu, Zn, Mn, Pb and Fe) and their effect on K, Ca and Mg availability in oil palm cultivated areas affected by bauxite mining activities using the combinations of geostatistic and geospatial analysis. A total of 64 soil samples were collected covering a total area of 420.21 ha by grid sampling technique. Spatial distributions of the heavy metals were determined using semivariogram and mapped using ArcGIS. The mean concentrations of Cu (138.94 ± 79.08 mg kg-1), Zn (233.55 ± 79.16 mg kg-1), Mn (847.88 ± 267.02) mg kg-1) and Fe (249 703.71 ± 101 408.72 mg kg-1) in this study were greater than the background values, the 95% ‘Investigation Levels’ determined for Malaysia soil and Dutch target values. Geoaccumulation index showed that the contamination was in the order of Fe> Cu>Pb>Zn> Mn. Semivariogram analysis of pH, Mn, Zn and Fe was aligned with the principal component analysis results, showing the contamination source originated from a similar identical source. In correlation to the nutrients, only Kex., was found to be affected by the contaminants. These results provide a useful basis for the related agencies in identifying hotspots for future rehabilitation programs.